Comparison of influence of high thoracic epidural anesthesia and central analgesia on hemodynamic during on-bypass coronary artery bypass grafting - V. A. Sobokar; S. N. Gritsenko; M. S. Potapenko (Zaporožskij Medicinskij Žurnal)
Objective. Despite some advantages, the use of high thoracic epidural anesthesia (HTEA) during cardiac operations may be discouraged by fear of adverse hemodynamic effects. Aim. To compare the hemodynamic effects of HTEA and central analgesia (CA) during on-bypass CABG.